Understanding survival analysis: actuarial life tables and the Kaplan–Meier plot. (2nd November 2019) - Barakat, Ahmed; Mittal, Aaina; Ricketts, David; Rogers, Benedict A
Abstract : Survival analysis is a set of methods used to study the time between enrollment in a study and the occurrence of an event of interest. Two methods are commonly used: actuarial life tables and the Kaplan–Meier approach for survival analysis. A good understanding of both these methods is useful when reading and appraising the literature concerning prognostic and interventional studies. Kaplan–Meier curves are widely used as they enable analysis of incomplete sets of data (i.e. after patients withdraw from studies or are lost to follow up). This review explains these two methods and gives practical examples of their use.